2021
DOI: 10.3389/fimmu.2021.698312
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-PDLIM1 Autoantibody as Diagnostic Marker in Ovarian Cancer

Abstract: BackgroundSerum autoantibodies (AAbs) against tumor-associated antigens (TAAs) could be useful biomarkers for cancer detection. This study aims to evaluate the diagnostic value of autoantibody against PDLIM1 for improving the detection of ovarian cancer (OC).MethodsImmunohistochemistry (IHC) test in tissue array containing 280 OC tissues, 20 adjacent tissues, and 8 normal ovarian tissues was performed to analyze the expression of PDLIM1 in tissues. Enzyme-linked immunosorbent assay (ELISA) was employed to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The role of MYL6 in OC is currently unknown, but it has been shown that MYL6 expression was upregulated in rhabdomyosarcoma ( Eichenmüller et al, 2007 ), and was negatively associated with cell migration in melanoma ( Vierthaler et al, 2022 ). Previous studies suggested that PDLIM1 was upregulated in OC ( Qiu et al, 2021 ), which was consistent with our findings ( Figure 6D ). PDLIM1 could inhibit tumor metastasis and EMT by interacting with E-cadherin/β-catenin adhesion complex, inhibiting the Hippo signaling pathway ( Chen et al, 2016 ; Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…The role of MYL6 in OC is currently unknown, but it has been shown that MYL6 expression was upregulated in rhabdomyosarcoma ( Eichenmüller et al, 2007 ), and was negatively associated with cell migration in melanoma ( Vierthaler et al, 2022 ). Previous studies suggested that PDLIM1 was upregulated in OC ( Qiu et al, 2021 ), which was consistent with our findings ( Figure 6D ). PDLIM1 could inhibit tumor metastasis and EMT by interacting with E-cadherin/β-catenin adhesion complex, inhibiting the Hippo signaling pathway ( Chen et al, 2016 ; Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…This protein has a PDZ domain at the amino terminus, while at the carboxyl terminus is a LIM domain. PDLIM1 regulates the actin cytoskeleton organization and is involved in the cells’ morphological changes and migration [ 35 ]. The expression level of PDLIM1 impacts the assembly of focal adhesion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Combining anti-BRCA1-associated RING domain 1 (BARD1) AABs and serum CA125 levels showed a sensitivity of 91% and a specificity of 95% among 741 samples [ 106 ]. Lastly, combining anti-PDZ and LIM domain 1 (PDLIM1) AABs and CA125 levels increased the AUC to 0.846, such that around 80% of patients could be detected [ 107 ].…”
Section: Potential Biomarkers For Ovarian Cancer Detectionmentioning
confidence: 99%